Handling Academic Stress Among Students In Indonesia: A Systematic Literature Review - Fahmy Ferdiyanto; I Gusti Ayu Agung Noviekayati; Suhadianto (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Academic activities at school present various challenges for students. The obligations assigned must be completed immediately, sometimes becoming a demand that causes boredom both internally and externally. The purpose of this study is to collect and identify interventions to reduce academic stress levels. This study uses a systematic literature review (SLR). The literature review procedure follows the PRISMA model. Based on the selection process using the PRISMA model, 83 articles were identified. After further screening according to the PRISMA 2020 guidelines, 13 articles were deemed suitable and aligned with the research criteria and objectives for analysis. Based on the analysis and literature review, it was found that in the application of several interventions used on participants experiencing academic stress, counseling, stress management techniques, and therapy were effective in reducing stress levels. For future research, it is recommended to consider the application of interventions in various contexts, such as understanding the participants' conditions, formulating intervention plans tailored to their needs, using a systematic approach applicable in both individual and social contexts, and encouraging active participation from the participants and their social environment..